(untitled) (Journal of Oriental Studies, 2019)
In any language without interjections it would be extremely difficult to express diverse feelings and emotions, since this part of speech gives the language a rich color. Interjections and onomatopoeic words occupy a special position among the lexical and grammatical categories of words. They differ from significant words in that they do not perform a nominative function, do not change in terms of persons, numbers and cases, are not members of a sentence. Interjections differ from official words in that they do not serve to connect members of a sentence or parts of a sentence (as unions), do not express the re lationship between the main and dependent words (as prepositions), and do not give words (statements) additional semantic and emotionalexpressive shades (like particles). On morphological and syntactic features, as well as on the nature of their correlation with reality, interoperative words adjoin interjection, imitating the sounds of living or inanimate nature. Key words: Russian and Turkish languages, grammar, interjections, onomatopoeic words.